A sequence-independent strategy for amplification and characterisation of episomal badnavirus sequences reveals three previously uncharacterised yam badnaviruses - Bömer, M.; Turaki, A.A.; Silva, G.; Kumar, P. Lava; Seal, S.E. (MDPI, 2016)
Yam (Dioscorea spp.) plants are potentially hosts to a diverse range of badnavirus species (genus Badnavirus, family Caulimoviridae), but their detection is complicated by the existence of integrated badnavirus sequences in some yam genomes. To date, only two badnavirus genomes have been characterised, namely, Dioscorea bacilliform AL virus (DBALV) and Dioscorea bacilliform SN virus (DBSNV). A further 10 tentative species in yam have been described based on their partial reverse transcriptase (RT)-ribonuclease H (RNaseH) sequences, generically referred to here as Dioscorea bacilliform viruses (DBVs). Further characterisation of DBV species is necessary to determine which represent episomal viruses and which are only present as integrated badnavirus sequences in some yam genomes. In this study, a sequence-independent multiply-primed rolling circle amplification (RCA) method was evaluated for selective amplification of episomal DBV genomes. This resulted in the identification and characterisation of nine complete genomic sequences (7.4–7.7 kbp) of existing and previously undescribed DBV phylogenetic groups from Dioscorea alata and Dioscorea rotundata accessions. These new yam badnavirus genomes expand our understanding of the diversity and genomic organisation of DBVs, and assist the development of improved diagnostic tools. Our findings also suggest that mixed badnavirus infections occur relatively often in West African yam germplasm.